1991
DOI: 10.1128/iai.59.10.3351-3359.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunization with Porphyromonas gingivalis and Prevotella intermedia on progression of ligature-induced periodontitis in the nonhuman primate Macaca fascicularis

Abstract: The nonhuman primate (Nhp) has proven to be a useful model of human periodontitis. This study describes the immunological characteristics of this model and the ability of active immunization to interfere with ecological changes in the microbiota and its associated disease symptoms. Nhps were parenterally immunized with whole-cell antigens of Porphyromonas gingivalis and Prevotella intermedia. The immunization elicited an approximate 2-log increase in serum immunoglobulin G (IgG), IgM, and IgA isotype antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 53 publications
6
104
1
1
Order By: Relevance
“…For example, Persson et al (1994) showed that vaccination with P. gingivalis provided protection against experimentally induced periodontitis in the monkey model. In contrast, Ebersole et al (1991) could not demonstrate any protection against experimental periodontitis, using P. gingivalis vaccine in the same model. However, no study has raised the possibility, or tested the hypothesis, that these differences are because of the use of different adjuvants in the vaccine.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, Persson et al (1994) showed that vaccination with P. gingivalis provided protection against experimentally induced periodontitis in the monkey model. In contrast, Ebersole et al (1991) could not demonstrate any protection against experimental periodontitis, using P. gingivalis vaccine in the same model. However, no study has raised the possibility, or tested the hypothesis, that these differences are because of the use of different adjuvants in the vaccine.…”
Section: Discussionmentioning
confidence: 71%
“…Studies on the development of a vaccine to prevent periodontal disease by immunization with antigens from Porphyromonas gingivalis have produced variable and conflicting results (Page 2000). Several studies using both mice and primates have demonstrated that immunization with P. gingivalis results in protection against experimentally induced periodontal destruction (Okuda et al 1988, Persson et al 1994, Genco et al 1998, Gonzalez et al 2003, while other animal studies have been unable to demonstrate protection (Ebersole et al 1991, Moritz et al 1998). In humans, numerous studies have demonstrated that patients with periodontitis mount a humoral immune response to plaque bacteria during the course of their disease (Tew et al 1985, Mooney et al 1997, and antibody titres to P. gingivalis have been shown to be inversely related to disease severity (Okuda et al 1988, Mooney et al 1997).…”
mentioning
confidence: 99%
“…[43][44][45][46] As we have shown previously, nonhuman primates can be vaccinated with Pg or selected components resulting in significant increases in local and systemic IgG antibodies leading to decreased clinical disease in a ligature-induced model. 19,27,28 As such, numerous studies in rodent, canine, and nonhuman primate models support the finding that active vaccination with Pg or its component parts can significantly decrease induced periodontitis. [45][46][47][48][49] Our findings suggest that the elevated antibodies in humans that occur in response to naturally occurring periodontitis can help to ameliorate this process, potentially through opsonization of oral bacteria, which suppress the osteoclast-mediated bone loss in periodontitis.…”
Section: Discussionmentioning
confidence: 92%
“…Bacteria were fixed in 0.5% buffered formal saline by incubation at RT overnight. 19 Once the cells have been fixed, they were washed extensively in PBS-EDTA and stored at 4°C in a concentrated form. Heat-killed Pg were prepared following incubation of cultures at 70°C in water bath for 1 hour, pelleted and stored in PBS at 4°C until usage.…”
Section: Bacterial Culturesmentioning
confidence: 99%
See 1 more Smart Citation